Miocene magnetostratigraphy of ODP Site 199-1218 in the equatorial Pacific - Luca Lanci; Josep M Parés; James E T Channell; Dennis V Kent (PANGAEA, 2004)
Pliocene and Miocene magnetostratigraphy from ODP Site 1218 (Equatorial Pacific) has been obtained by measurements made on u-channel samples, augmented by about 50 discrete samples. U-channel samples were measured at 1 cm intervals and stepwise demagnetized in alternating fields up to a maximum peak field of 80 mT. The component magnetization directions were determined by principal component analysis for demagnetization steps in the 20-60 mT peak field range. A relatively small number of discrete samples were subject to both thermal and alternating field (AF) demagnetization and gave results compatible with u-channel measurements. Magnetostratigraphy from u-channel samples are compared with shipboard data that were based on blanket demagnetization at peak AF fields of 20 mT. U-channel measurements add more detail to the magnetostratigraphic record and allow identification of thin polarity zones especially in the upper part of the section were the sedimentation rates are very low (~2 m/Myr). The component magnetization directions determined from u-channel measurements also gave more reliable and precise estimates of inclination (paleolatitude). The magnetostratigraphy from Site 1218 can be unambiguously correlated with the reference geomagnetic polarity time scale and gives a means of dating the sedimentary sequence. Both Miocene-Pliocene and Oligocene-Miocene stage boundaries were easily identified from the magnetostratigraphic record. Although calculation of paleomagnetic poles is hindered by the low precision of the cores extquotesingle azimuthal orientation, the data from both u-channel and discrete samples allow determination of the paleolatitude of the Site through time with good precision. Paleomagnetic data indicate that the paleolatitude of Site 1218 has increased form nearly equatorial latitude in the Oligocene to its present-day latitude close to 9°N. Within the precision of the paleomagnetic data, this is in agreement with current predictions of plate motion models based on fixed hotspots.
Supplement to: Lanci, L et al. (2004): Miocene magnetostratigraphy from Equatorial Pacific sediments (ODP Site 1218, Leg 199). Earth and Planetary Science Letters, 226(1-2), 207-224, https://doi.org/10.1016/j.epsl.2004.07.025